Two Days of the “Six Day War” - SHUBIN Vladimir Gennadievich (Ученые записки Института Африки Российской академии наук)
The article is based on the information of the author, who as officer of the 10th Main Directorate of the Soviet General Staff spent two days in Egypt during the Six Day War between Israel and the Arab states. It briefly analyzes the history of Moscow’s relations with Cairo after the 1952 revolution, particularly in the military field, and notes that the Soviet military leadership overestimated the combat capability of the Armed Forces of the United Arab Republic, as the Arab Republic of Egypt was then called. Although by June 1967 the situation in the Middle East was rather tense, the war was not expected by Moscow on the day Israel attacked Egypt, and its quick success, especially the defeat of the Egyptian Air Force, was a shock to Cairo and Moscow.